Carbon nanotubes enhanced Seebeck coefficient and power factor of rutile TiO2. Issue 12 (28th March 2015) - Lai, Yao-Cheng; Tsai, Hsin-Jung; Hung, Chia-I; Fujishiro, Hiroyuki; Naito, Tomoyuki; Hsu, Wen-Kuang
<x xml:space="preserve">Abstract</x> Ti–C substitution occurs when carbon nanotubes were thermally dispersed in rutile TiO2 and the electrical conductivity as well as Seebeck coefficient were simultaneously promoted at a low filling fraction of tubes.